Violet Cane: A Breaker of Codes and Moulds. Issue 5 (26th September 2022) - Gandy, Rob; Lorenzo-Arribas, Altea; Startup, Richard
Abstract: She ditched her PhD to help defeat the Nazis, and is remembered as a kind teacher and funny friend. Here, Rob Gandy, Altea Lorenzo-Arribas and Richard Startup celebrate the life and work of pioneering British statistician Professor Violet Cane